NOMINA DALAM PUISI-PUISI KARYA CARL SANDBURG - Merien, Efraim Wayambo (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI)
ABSTRACT This research entitled “Nouns in the Carl Sandburg’ Poetries“ is written to fulfill the requirement of finishing S1 degree in English Department, Faculty of Letters Sam Ratulangi University. The aim of this research is to identify, describe and analyze Nouns in the poetries in term of its types. The theorist that will be use in research, Tarigan, Aarts and Aarts and Marcella Frank concept. In this case in classified and analyzing data, interns of form and meaning. The result of this research shows that the types of nouns used in the poetries by Carl Sandburg are ; those that are classified by meaning and classified by form. Noun classified by meaning are proper noun, concrete and abstract noun, countable and uncountable noun, and collective noun, whereas noun classified by form are compound noun, adjective form used as noun and verb form used as noun. __________________ Keywords: Noun, Carl Sandburg’s Poetries.